A class of hydrazones are active against non-replicating Mycobacterium tuberculosis - Bonnett, Shilah A. (PLoS One, 2018)
There is an urgent need for the development of shorter, simpler and more tolerable drugs to treat antibiotic tolerant populations of Mycobacterium tuberculosis. We previously identified a series of hydrazones active against M. tuberculosis. We selected five representative compounds for further analysis. All compounds were active against non-replicating M. tuberculosis, with two compounds demonstrating greater activity under hypoxic conditions than aerobic culture. Compounds had bactericidal activity with MBC/MIC of < 4 and demonstrated an inoculum-dependent effect against aerobically replicating bacteria. Bacterial kill kinetics demonstrated a faster rate of kill against non-replicating bacilli generated by nutrient starvation. Compounds had limited activity against other bacterial species. In conclusion, we have demonstrated that hydrazones have some attractive properties in terms of their anti-tubercular activity.